2022
DOI: 10.1038/s41598-022-09592-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic strategy for melanoma based on albendazole and the CDK4/6 inhibitor palbociclib

Abstract: Although an increasing number of patients benefit from immunotherapy and targeted therapies, melanoma remains incurable with increasing incidence. Drug repositioning and repurposing is an alternative strategy to discover and develop novel anticancer drugs or combined therapeutic regimens. In this study, we demonstrated that albendazole (ABZ), an Food and Drug Administration (FDA)-approved broad-spectrum antiparasitic agent, significantly inhibits the proliferation of melanoma cells in vitro and in vivo. RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These studies reveal that Palbociclib treatment effectively disrupts the CDK4/CDK6–cyclin D complex, leading to the inhibition of Rb protein phosphorylation and the prevention of E2F release. This inhibition of E2F-mediated transcription results in the down-regulation of cell cycle regulatory protein expression, inducing G1-phase cell cycle arrest in human melanoma A375P cells [ 35 , 36 ]. In our study, we corroborated the impact of palbociclib on A375P cells, confirming that treatment with 2 µM palbociclib reduces the contribution of the S and G2/M populations in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reveal that Palbociclib treatment effectively disrupts the CDK4/CDK6–cyclin D complex, leading to the inhibition of Rb protein phosphorylation and the prevention of E2F release. This inhibition of E2F-mediated transcription results in the down-regulation of cell cycle regulatory protein expression, inducing G1-phase cell cycle arrest in human melanoma A375P cells [ 35 , 36 ]. In our study, we corroborated the impact of palbociclib on A375P cells, confirming that treatment with 2 µM palbociclib reduces the contribution of the S and G2/M populations in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, thiabendazole, another antiparasitic benzimidazole, has proven to be effective at inhibiting proliferation of several GB cell lines by the downregulation of mini-chromosome maintenance protein 2 (MCM2) [ 57 ]. Shu et al demonstrated that ALB plus Palbociclib, a cyclin kinase 4/6 (CDK4/6) inhibitor, synergistically suppresses melanoma cell proliferation in vitro and in vivo, by the dual arrest of cell cycle progression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro screening system showed a broad-spectrum anti-parasitic compound IVM among 231 candidate small molecular compounds in the database of Drug Bank significantly reduced CTSB-induced NETs formation, with no effect on tumor cell viability. The prior investigation on repositioning drugs, such as mefloquine and albendazole have demonstrated to promote cancer treatment by targeting cell cycle arrest in melanoma cells ( 37 , 38 ). IVM is widely used in both animals and human as an FDA-approved parasiticide ( 39 ).…”
Section: Discussionmentioning
confidence: 99%